PENGELOLAAN DATA BILLING COLLECTION PADA DASHBOARD EKSEKUTIF DAN OPERASIONAL - Kikim Mukiman; Rudi Budi Agung; Muhammad Ridick (LPPM Unbaja, 2026)
The management of billing collection data, often sourced from fragmented systems, manual processes, and a lack of real-time visibility, poses a significant risk of revenue leakage and hinders Revenue Assurance effectiveness. This study aims to design and build a Business Intelligence (BI) solution to address these issues. Adopting the Design Science Research Methodology (DSRM), the research implements an end-to-end Extract, Transform, Load (ETL) pipeline to integrate data from various file formats (TXT, CSV). The implemented technologies include Google Drive as a data repository, Microsoft Excel (Power Query) as the ETL engine, and Looker Studio for visualization. The outcome is a functional system comprising an automated ETL workflow and two interactive dashboards tailored for different audiences: an Executive Dashboard for strategic monitoring of Key Performance Indicators (KPIs) and long-term trends, and an Operational Dashboard that provides detailed, actionable data for daily collection activities. System evaluation via black-box testing confirmed that all functionalities performed as designed. The developed artifact successfully enhances data visibility, supports evidence-based decision-making, and directly contributes to Revenue Assurance by providing a tool for proactive and effective monitoring and mitigation of uncollectible receivables.